Perceived Benefits for Customer Service of ITIL IT Control Use - Egeler, Markus (Auckland University of Technology, 2008)
IT service management is becoming more and more important in the current business environment. Especially the IT Infrastructure Library (ITIL) is a widely adopted and accepted IT service management framework (Wagner 2006). Organizations that adopt one of the IT service management frameworks expect to achieve a large range of benefits through the use of the frameworks. The major benefits that are expected to be realised include reduced costs, IT services that are tailored to the business needs, a higher quality of IT services, and improved customer satisfaction (OGC 2007a). Despite the growing importance and acceptance of IT service management and ITIL, there is not much literature that is concerned with the benefits that can be realised when one of the relevant IT service management frameworks is in place. Only a few studies were published in conference proceedings (e.g. Hochstein et al. 2005, Potgieter et al. 2005, Cater-Steel et al. 2006). Even though these studies were able to confirm some of the claims made by the Office of Government Commerce (OGC), the publisher of the ITIL series, there are still a lot of claims that are not evaluated to date. This thesis is taking a Monte-Carlo method based simulation approach to identify some of the benefits of the ITIL for customer service. To achieve this, an initial research model was developed that represents the four most likely benefits for customer service of the use of ITIL and their relationship with customer service and the generation of business value. Subsequently the different path ways for the relationships were explored and models for each of the possible paths were designed. These models include a mediated model, an unmediated model and a partially mediated model. After defining the estimates and constraints for the simulation, the simulation was executed using a MS Excel spreadsheet. The simulation results presented a large amount of data for each of the models and their relationships. The models produced normal distributions and showed stability for changed input and throughput parameters. The analysis of the findings showed that the changes in estimates for each of the models and the associated results of the simulation followed a linear pattern. The linearity of the models combined with the normal distribution of the results offers a lot of opportunities for the use of the developed models. A further enhancement through a test with real-life data could provide the basis for a tool to quantitatively predict the impact of an ITIL implementation on customer service and the creation of value for the business. In addition the four most likely contributors to improved customer service based on the use of ITIL have been identified from a literature review. The identified contribution towards improved customer service of these four beneficiary factors is supported by the results of the simulation. Therefore the results of this thesis provide the research community with a model that could provide the basis for further exploration of the beneficiary effects of ITIL on customer service.
Keywords: Information technology infrastructure library; Quantitative approach; Information technology; Business strategy; Capability maturity; IT service management